1990
DOI: 10.1002/jcp.1041430104
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin induces superoxide anion release from human endothelial cells

Abstract: The time-dependent release of superoxide anion (O2-) from bradykinin (Bk)-stimulated human umbilical vein endothelial cells (EC) was measured as the superoxide dismutase-inhibitable reduction of ferricytochrome C employing a novel application of microspectrophotometry. In the absence of Bk, O2- release by EC was not detectable. EC exposure to Bk (10(-6) to 10(-5) M) resulted in a rapid release of O2-. The release of O2- occurred within 5 minutes of exposure. O2- release was partially inhibited by indomethacin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(62 citation statements)
references
References 22 publications
2
60
0
Order By: Relevance
“…It plays a central role in the arachadonic acid pathway and PGH 2 production. PGH 2 is an important precursor for PGI 2 released by endothelial cells to modulate platelet activity and smooth muscle cell contractility (Kukreja et al 1986;Holland et al 1990). Cyclooxygenase produces O 2 ·-through its ability to oxidize NADPH and alternative substances to NADP·, which autoxidizes O 2 resulting in O 2 ·- (Kukreja et al 1986).…”
Section: Cyclooxygenasementioning
confidence: 99%
See 1 more Smart Citation
“…It plays a central role in the arachadonic acid pathway and PGH 2 production. PGH 2 is an important precursor for PGI 2 released by endothelial cells to modulate platelet activity and smooth muscle cell contractility (Kukreja et al 1986;Holland et al 1990). Cyclooxygenase produces O 2 ·-through its ability to oxidize NADPH and alternative substances to NADP·, which autoxidizes O 2 resulting in O 2 ·- (Kukreja et al 1986).…”
Section: Cyclooxygenasementioning
confidence: 99%
“…Cyclooxygenase produces O 2 ·-through its ability to oxidize NADPH and alternative substances to NADP·, which autoxidizes O 2 resulting in O 2 ·- (Kukreja et al 1986). Cyclooxygenase is also capable of generating significant quantities of ROS while producing prostaglandins such as PGH 2 (Holland et al 1990;Marshall et al 1990). …”
Section: Cyclooxygenasementioning
confidence: 99%
“…Previous studies have shown O 2 .7 production by endothelial cells treated with a Ca 2+ -ionophore or bradykinin (Katusic & Vanhoutte, 1989;Holland et al, 1990) and also by GTN, a NO donor (Dikalov et al, 1998). In general, sites of O 2 .7 synthesis include membrane-bound NAD(P)H oxidases (MuÈ nzel et al, 1995), xanthine oxidase (Katusic & Vanhoutte, 1989), mitochondrial electron transport chain (Jansson et al, 1993), cytochrome P450 oxidase (Jansson et al, 1993) and cyclo-oxygenase (Holland et al, 1990).…”
Section: Introductionmentioning
confidence: 98%
“…In general, sites of O 2 .7 synthesis include membrane-bound NAD(P)H oxidases (MuÈ nzel et al, 1995), xanthine oxidase (Katusic & Vanhoutte, 1989), mitochondrial electron transport chain (Jansson et al, 1993), cytochrome P450 oxidase (Jansson et al, 1993) and cyclo-oxygenase (Holland et al, 1990). In a recent study of rat aortic endothelial cells (Puey et al, 1998), O 2 .7 production in response to angiotensin II was blocked by pretreatment with L-NMMA, an inhibitor of eNOS, indicating that eNOS is yet another site of O 2 .7 production.…”
Section: Introductionmentioning
confidence: 99%
“…The excessive production of ROS from endogenous and exogenous sources disrupts many functions in living cells [8]. The main cellular sources of ROS in the lung include not only neutrophils, eosinophils and alveolar macrophages [9], but also alveolar epithelial cells, bronchial epithelial cells and endothelial cells [10,11]. The generation of ROS in the lungs is enhanced after exposure to numerous exogenous chemical and physical agents, which include mineral dusts, ozone, nitrogen oxides, ultraviolet and ionizing radiation [12,13] and tobacco smoke [14].…”
Section: Introductionmentioning
confidence: 99%